An evaluation of "tiếng Anh 5" textbook in Tra Vinh province - Nguyễn Thị Hoàng Mụi (Trường Đại học Trà Vinh, 2020)
This study aims at finding the teachers’ perceptions towards strengths and weaknesses of “Tiếng Anh 5” textbook (designed by MOET in collaboration with Macmillan East Asia), and then recommendations from teachers for those weaknesses to have a better improvement for the future republication of this textbook.